EVALUASI KESESUAIAN LAHAN TANAMAN DURIAN DESA PAPUALANGI, KABUPATEN GORONTALO UTARA - Ahmad Syamsu Rijal (Universitas Tamansiswa Padang, 2019)
The purpose of this study is to determine the land suitability class for durian plants and the factors that affect land suitability for land classes in the region. This research was conducted in Papualangi Village with a height of 226 meters above sea level and is located on the edge of a public road to Cempaka Putih village. Location is chosen based on the presence of outcrops that can facilitate the conduct of research on land on the ground. To analyze the existence of land suitability in Papualangi village, there are several plants such as durian, rambutan, langsat / duku, cocoa, cloves, etc. This research was conducted using direct observation methods in the field to produce quantitative data. The results obtained are different land suitability levels for each factory and the determinants of land suitability are different from each other. From the results obtained it can also be concluded that the soil in Papualangi village is suitable for planting durian, rambutan, cloves, cocoa, robusta coffee, coconut and strawberry, and is more suitable for growing crops such as langsat, corn and tea. Land suitability can be affected by temperature, drainage, texture, nutrient retention, available nutrients, and land slope.